EUR 15 million invested for mitigation action in Thailand's rice sector - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
In June 2018, the NAMA Facility approved the EUR 14,900,000 funding for a pioneering NAMA Support Project on rice in Thailand. This 5-year project is expected to generate at least EUR 21.5 million more of private sector investments.